Speech Outcome Evaluation After Two-Flap Palatoplasty In Plastic Surgery Division Cipto Mangunkusumo Hospital: A Retrospective study - Bangun, Kristaninta; Handayani, Siti; Djoenaedi, Intania; Wahyuni, Luh Karunia (Jurnal Plastik Rekonstruksi, 2012)
One of the primary goal of cleft palate repair is to provide an intact mechanism for normal speech production. The purpose of this study is to evaluate the two-flap mucoperiosteal palatoplasty procedure on speech outcomes in patients undergoing surgical repair before the age of 2 years. A retrospective analysis study was done on 22 children with complete unilateral cleft palate (with or without cleft lip) who underwent two-flap palatoplasty between year 2002 to 2006 at Cipto Mangunkusumo Hospital. Evaluation was performed by a speech pathologist for pattern of articulation, hypernasality, intelligibility, and velopharyngeal competence. Palatoplasty were performed after 2 year-old in 11 patients and before 2 year-old in 11 patients. Speech of the 22 children postpalatoplasty was evaluated perceptually from standardised tape recordings. Velopharyngeal competence in patients who underwent palatoplasty before 2 year-old compared to after 2 year-old were 72.7% good, 18.2% fair and 9.1% poor versus 54,5% good, 9,1% fair and 36,4% poor respectively. Two-flaps mucoperiosteal palatoplasty performed before the age of 2 years old shows better spepolech outcome in all parameters, although the numbers are not statistically significant. Further prospective study with larger sample is needed.